When Compliance Meets Perception: A Theory of Planned Behavior-Based Study of Ethical Tax Evasion - Machfuzhoh, Asih; Puspanita, Intan (Jurnal Riset Akuntansi Terpadu, 2025)
This study examines the influence of taxation systems and fiscal discrimination on ethical perceptions of tax avoidance within the framework of the Theory of Planned Behavior (TPB). Ethical perceptions are important indicators in understanding voluntary tax compliance, particularly among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. An explanatory quantitative approach was used with data from 157 MSME taxpayers, analyzed using multiple linear regression. The results indicate that the tax system has a negative effect, while fiscal discrimination has a positive effect on ethical perceptions of tax avoidance. However, both effects are not statistically significant. The model only explains 5.9% of the variation in ethical perceptions, indicating the presence of other factors not captured in the model. This study contributes to strengthening the discourse on fair fiscal governance and emphasizes the importance of considering both technical aspects and perceptions of fairness in tax reform, in line with Sustainable Development Goal (SDG) 16.